1988
DOI: 10.1111/j.1365-2265.1988.tb03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Thyroid Cancer

Abstract: Ten of 502 patients presenting with thyroid cancer were hyperthyroid due to Graves' disease (4 patients), multinodular goitre (3), an autonomous functioning nodule (1) and a large functioning tumour (2). In addition eight patients had a past history of Graves' disease and four of hyperthyroidism associated with multinodular goitre. Mortality in patients with Graves' disease and with multinodular goitre appeared similar to that of other patients of comparable age. Both patients with large functioning tumours di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Yano et al compared the features of 154 cases of papillary thyroid cancers diagnosed in patients with Graves' disease to a euthyroid group with thyroid cancer [ 46 ] and did not fi nd signifi cant diff erences in multifocality, lymph node metastases, or distant metastases between the Graves' disease and the euthyroid group. Edmonds et al, in their study with 502 patients with thyroid cancer, reported similar mortality rates when comparing patients with Graves' disease and with multinodular goiter to that of euthyroid patients matched for age [ 45 ] . All the above mentioned studies are retrospective and explore diff erent clinical or histological parameters and therefore are not totally comparable.…”
Section: Aggressivenessmentioning
confidence: 76%
“…Yano et al compared the features of 154 cases of papillary thyroid cancers diagnosed in patients with Graves' disease to a euthyroid group with thyroid cancer [ 46 ] and did not fi nd signifi cant diff erences in multifocality, lymph node metastases, or distant metastases between the Graves' disease and the euthyroid group. Edmonds et al, in their study with 502 patients with thyroid cancer, reported similar mortality rates when comparing patients with Graves' disease and with multinodular goiter to that of euthyroid patients matched for age [ 45 ] . All the above mentioned studies are retrospective and explore diff erent clinical or histological parameters and therefore are not totally comparable.…”
Section: Aggressivenessmentioning
confidence: 76%
“…The need of protein factor(s) other than G proteins has recently been demonstrated for the functional expression of the formyl peptide receptor (Murphy and McDermott, 1991 (Weintraub TPO and TSHr et al, 1981;Faglia et al, 1987) and the much more frequent TSHr transcripts are Graves' disease where stimulation of the gland is due to the presence of thyroid stimulating autoantibodies (TSAB;McKenzie and Zakarija, 1989 (Burton et al, 1991; in control thyroids. Struthers et al, 1991 Although still a controversial matter, chronic hyperstimulation of the thyroid gland has been reported to correlate with a higher incidence of cancers (0.2-16.6%; Pacini et oglobulin promoter Edmonds and Tellez, 1988;Mazzaferri, 1990). Yene (Ledent et al, In our model, no obvious signs of malignancy could be 1991) to the thyroid found.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, we found only one similar case of functioning malignant thyroid nodule in association with Graves' disease in the series reported by Edmonds et al 11 The usual scintigraphic finding in thyroid carcinoma is a hypofunctioning (cold) nodule. In spite of the appearance of a functioning (warm) nodule on scintigraphy in our patient, this nodule harbored malignancy.…”
Section: Discussionmentioning
confidence: 84%
“…28,29 More recently, increasing reports on the possible carcinogenic role of TBII and other immunoglobulins in Graves' disease are seen in the literature. 11,15,30 All these findings suggest the possible carcinogenic role of Graves' immunoglobulins interacting with TSHreceptors producing thyroid hyperplasia and later neoplasia. Some recent reports showed that Graves' disease and Graves' immunoglobulins not only influence the development and genesis of thyroid carcinoma, but also affect the behavior of these tumors as they grow larger and behave more aggressively than those associated with autonomous thyroid nodules.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation